"Turn-On" Quinoline-Based Fluorescent Probe for Selective Imaging of Tau Aggregates in Alzheimer's Disease: Rational Design, Synthesis, and Molecular Docking - Elbatrawy, Ahmed A.; Hyeon, Seung Jae; Yue, Nan; Osman, Essam Eldin A.; Choi, Seung Hyeo; Lim, Sungsu; Kim, Yun Kyung; Ryu, Hoon; Cui, Mengchao; Nam, Ghilsoo (AMER CHEMICAL SOC, 2021)
Tau aggregation is believed to have a strong association with the level of cognitive deficits in Alzheimer's disease (AD). Thus, optical brain imaging of tau aggregates has recently gained substantial attention as a promising tool for the early diagnosis of AD. However, selective imaging of tau aggregates is a major challenge due to sharing similar beta-sheet structures with homologous A beta fibrils. Herein, four quinoline-based fluorescent probes (Qtau) were judiciously designed using the donor-acceptor architecture for selective imaging of tau aggregates. In particular, probe Qtau 4 exhibited a strong intramolecular charge transfer and favorable photophysical profile, such as a large Stokes' shift and fluorescence emission wavelength of 630 nm in the presence of tau aggregates. The probe also displayed a "turn-on" fluorescence behavior toward tau fibrils with a 3.5-fold selectivity versus A beta fibrils. In addition, Qtau 4 exhibited nanomolar binding affinity to tau aggregates (K-d = 16.6 nM), which was 1.4 times higher than that for A beta fibrils. The mechanism of "turn-on" fluorescence was proposed to be an environment-sensitive molecular rotor-like response. Moreover, ex vivo labeling of human AD brain sections demonstrated favorable colocalization of Qtau 4 and the phosphorylated tau antibody, while comparable limited staining was observed with A beta fibrils. Molecular docking was conducted to obtain insights into the tau-binding mode of the probe. Collectively, Qtau 4 has successfully been used as a tau-specific fluorescent imaging agent with lower background interference.